Detecting Abnormal Neuronal Activity in a Chronic Migraine Model by Egr1-EGFP Transgenic Mice - Wang, Fei; Jiang, Weiqing; Gao, Li; Liu, Chen; Deng, Mingzhu; Ren, Xiao; Zhu, Chenlu; Guan, Ji-Song; Wang, Yonggang (Frontiers in Neuroscience, 2021)
Chronic migraine (CM) is a highly disabling neurological disorder characterized by recurrent headache accompanied by a variety of sensory and/or emotional symptoms. However, the mechanisms of migraine onset and its chronicity have not been elucidated. The present study was designed to search for brain regions and neurons that were abnormally activated by CM and might be related to its pathogenesis and different concomitant symptoms. CM models were established here by repeated intraperitoneal injection of nitroglycerin (NTG) every other day for 9 days to early growth response gene 1 (Egr1)- enhanced green fluorescent protein (EGFP) transgenic mice, which allowed monitoring of neuronal activities in the whole brain. CM-related behaviors were recorded through head grooming test and light aversion assay. Elevation of Egr1 expression signals was detected in trigeminal nucleus caudalis (TNC), primary somatosensory cortex (SSp), lateral amygdala nucleus (LA), primary visual area (VISp) and temporal association areas (TEa) two hours after the last injection of NTG by immunofluorescence and digital slice scanning technology. Meanwhile, no change of Egr1 expression was found in auditory areas (AUD), CA1, ectorhinal area (ECT), piriform (PIR) and anterior cingulate area (ACC). Furthermore, with the strongest support by evidence-based medicine among the current limited oral treatments of CM, topiramate was administrated every day for 11 days from 2 days before the first NTG injection. The results showed that topiramate partially improved the photophobia behavior of CM models in the short-term with gradually weakened efficacy as the course of the disease prolonged. Meanwhile, NTG-induced increase in Egr1 expression was completely reversed in TNC, SSp and VISp and partially reduced in LA and TEa by topiramate at the same time point mentioned above. In conclusion, the current results suggested that the abnormal hyperactivities in TNC, SSp and VISp were associated with the pathogenesis of CM.